Designing of Hydraulic Ram Pump (International Journal of Engineering and Computer Science, 2015)
This paper describes the techniques and guidelines to successfully install the modern hydraulic ram pump. The proposed technique illustrates the methodology that can be used for the primary design considerations and applications in various ways. This Hydraulic ram pump plays an important role in areas which are not connected to national electricity grid. This method provides means of continuous water supply. Basic principle of working is ramming action of air inside pressure vessel.